CHALLENGES IN TEACHING GRAMMAR - Jumabayeva, Adolat (АКТУАЛЬНОЕ В ФИЛОЛОГИИ, 2021)
In the teaching of English as a second language, grammar is considered as one of the significant skills to master. While teaching and learning English both teachers and students face a number of difficulties in using grammar. This paper highlights the difficulties and challenges in teaching and learning English grammar